Unveiling the Impact of Education and Multicultural Personality on the Well-being of Generation Z in Schools - Fitri Feliana; Paidi Gusmuliana; Syafryadin Syafryadin (AL-ISHLAH: Jurnal Pendidikan, 2024)
In terms of aspects of students' school well-being, this paper will address multicultural education, dimensions of multicultural education, aspects of multicultural personality, school well-being, and the psychological dynamics of education and multicultural personality. This research utilized the Systematic Literature Review (SLR) method to identify, review, and interpret relevant articles on multicultural education and personality in Gen Z school well-being, focusing on a broad scope. From the given description, it can be inferred that multicultural education and personality in school well-being for Generation Z can be examined through two dimensions: social relations (loving aspect) and self-fulfillment (being aspect). Additionally, the research highlights the importance of inclusivity and diversity in educational practices, as they contribute significantly to students' sense of belonging and psychological comfort. Meanwhile, in multicultural education, it is imperative to consider both the school environment and the health state of children to fully meet their well-being in implementing multicultural education and fostering their individuality inside schools. This study also underscores the necessity of culturally responsive teaching methods and the role of educators in creating a supportive learning environment that recognizes and values individual differences. By doing so, schools can better support the holistic development of students, ensuring they thrive both academically and personally.